Concomittan Hyperuricemia and Abcess Mid Thoracic Region: The Use of Dual Energy CT Scan - Feda Makkiyah (Fakultas Kedokteran Universitas Lambung Mangkurat, 2021)
Abstract: Dual energy scan was performed to differentiate any collection associated with calsium. Case report. This 23 year old man showed severe hyperuricemia and mid thoracic pain and MRI showed collection over posterior epidural thecal sac over T3 until T9. Dual energy CT scan was performed to assess uric acid crystal over thoracic region. The CT result was negative. He was treated over intravenous antibiotic and pain medication. His pain improved progressively and laboratory results showed towards normal value and he was discharged on day twelveth. Conclusion. This case report showed the comprehensive diagnostic tool to yield out the aetiology of thoracal epidural collection, despite negative result. Keywords: Hyperuricemia, abcess, mid thoracic, dual energy, CT scan